1990
DOI: 10.1121/1.399718
|View full text |Cite
|
Sign up to set email alerts
|

Response timing constraints on the cortical representation of sound time structure

Abstract: The precision of spike response timing of 94 primary auditory cortex neurons was studied using conventional extracellular recording techniques in barbiturate-anesthetized cats to which tone- and/or noise-burst stimuli were presented using sealed sound delivery systems. Precision of spike timing was indexed using the standard deviation of the first-spike latent period in responses evoked by repeated presentation of tonal stimuli systematically varied in frequency, amplitude, and/or repetition rate. Within a neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
66
1
1

Year Published

1992
1992
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(76 citation statements)
references
References 0 publications
8
66
1
1
Order By: Relevance
“…Auditory neurons in cortex increase synchrony and precision of firing with increases in stimutials were particularly well-formed in amplitude and morphology. Moreover, her perception of fine-grained lus intensity (Phillips and Hall 1990). Possibly IT cannot profit from this mechanism because, in her differences along a /ba-wa/ continuum was extraordinarily good, possibly reflecting neural reorganization case, neural input into auditory cortex lacks onset precision in the first place.…”
Section: Fig 5 P1/n1mentioning
confidence: 97%
See 2 more Smart Citations
“…Auditory neurons in cortex increase synchrony and precision of firing with increases in stimutials were particularly well-formed in amplitude and morphology. Moreover, her perception of fine-grained lus intensity (Phillips and Hall 1990). Possibly IT cannot profit from this mechanism because, in her differences along a /ba-wa/ continuum was extraordinarily good, possibly reflecting neural reorganization case, neural input into auditory cortex lacks onset precision in the first place.…”
Section: Fig 5 P1/n1mentioning
confidence: 97%
“…A high degree of temporal precision nous activity across a population of neurons. It should be emphasized, however, that cortical potentials reflect is also required to encode rapid formant transitions (Phillips et al 1989;Phillips and Hall 1990). In the case neural synchrony differently than the ABR.…”
Section: Fig 5 P1/n1mentioning
confidence: 99%
See 1 more Smart Citation
“…15 The precision of the first neural firing that responds to the onset of sound is proportional to the neural response latency. Phillips and Hall 13 found latency as short as 0.45 -1.5 ms for first neural firing in the auditory cortex of cats. These values are very close to those observed in the cochlear nerve and the cochlear nucleus, suggesting that temporal fidelity for transitory responses is preserved in afferent pathways until the primary auditory cortex.…”
Section: Introductionmentioning
confidence: 99%
“…5,10,11 Other studies, however, have shown that processing is more central. [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] Temporal resolution depends on the separation of different auditory stimuli; the role of the initial part of the stimulus and the coding precision of this response are crucial. 19,24 Auditory cortex neurons are particularly sensitive to these initial transitory stimuli, including the beginning of periodic events, the incident modulation of other periodic signals o the acoustic events that occur naturally in vocalization.…”
Section: Introductionmentioning
confidence: 99%